2015
DOI: 10.1590/2317-1782/20152014078
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic fatigue of orbicular oris muscles during exercises in mouth and nasal breathing children

Abstract: DescritoresElectromyographic fatigue of orbicular oris muscles during exercises in mouth and nasal breathing children Fadiga eletromiográfica dos músculos orbiculares da boca durante exercícios em crianças respiradoras orais e nasais ABSTRACT Purpose: To investigate the process of fatigue in orbicularis oris muscles by analyzing the median frequency of electromyographic signal and the referred fatigue time, according to the breathing mode and the facial pattern. Methods: The participants were 70 children, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
0
10
0
6
Order By: Relevance
“…The breath, physiological, vital and innate function of the human being, protects the upper airway and allows the satisfactory development of the craniofacial complex if performed correctly [1][2][3][4] . For proper nasal breathing, lip sealing is indispensable for generating a differentiation system of intra and extra-oral pressures in the so-called Oronasopharyngeal Space.…”
Section: Introductionmentioning
confidence: 99%
“…The breath, physiological, vital and innate function of the human being, protects the upper airway and allows the satisfactory development of the craniofacial complex if performed correctly [1][2][3][4] . For proper nasal breathing, lip sealing is indispensable for generating a differentiation system of intra and extra-oral pressures in the so-called Oronasopharyngeal Space.…”
Section: Introductionmentioning
confidence: 99%
“…As for the methodology of the studies, it was found that most studies divided the sample into two groups (mouth and nasal breathers) 14,15,17,19,[21][22][23][24][25][26] with subgroups 18,27,28 to compare the electromyographic findings of the muscles studied in the two populations. As for publication journals, there is a wide variety of journals.…”
Section: Fadiga Eletromiográfica Dos Músculos Orbiculares Da Boca Durmentioning
confidence: 99%
“…A single study addressed the impact of myofunctional therapy by performing an electromyographic assessment before and after a speech-language pathology therapy 23 , and two other studies assessed muscle electrical activity after months of physical therapy sessions 21,22 , while the other studies used the electromyography to complement the initial clinical assessment, detect the muscle activity pattern 14,15,17,18,2 0,24,25,27,28 and to assist in the diagnosis 26 . The literature in the speech-language pathology area understands the sEMG as a reliable tool for a reliable assessment, diagnosis and treatment related to speech-language pathology 24,26 .…”
Section: Fadiga Eletromiográfica Dos Músculos Orbiculares Da Boca Durmentioning
confidence: 99%
“…Estudos recentes utilizaram a eletromiografia de superfície para analisar a função muscular em indivíduos com respiração nasal e oral, apresentando resultados significantes para a literatura (HENNIG et al, 2009;BOTON et al, 2011;BUSANELLO-STELLA et al, 2015). Todavia, é importante que mais pesquisas investiguem a função muscular em indivíduos com respiração oral, para facilitar a atuação clínica frente às alterações estruturais e funcionais decorrentes dessa patologia.…”
Section: Introductionunclassified